2007
DOI: 10.1136/hrt.2006.091751
|View full text |Cite
|
Sign up to set email alerts
|

Nebivolol improves coronary flow reserve in patients with idiopathic dilated cardiomyopathy

Abstract: Background: Impaired coronary flow reserve (CFR) is a significant predictor of poor prognosis in patients with idiopathic dilated cardiomyopathy (IDC). Nebivolol reduces mortality and morbidity in patients with heart failure and left ventricular dysfunction, including cases caused by IDC. Objective: To assess the effects of nebivolol on CFR in patients with IDC. Methods: CFR was measured in 21 clinically stable patients with IDC (mean (SD) ejection fraction 35.7 (6.2)) at baseline and after 1 month of treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 24 publications
3
28
0
1
Order By: Relevance
“…Nebivolol also was shown to significantly improve CMD in patients with idiopathic dilated cardiomyopathy [11]. CFR was measured in 21 patients at baseline and 1 month after treatment and was found to increase significantly.…”
Section: Dilated Cardiomyopathymentioning
confidence: 98%
“…Nebivolol also was shown to significantly improve CMD in patients with idiopathic dilated cardiomyopathy [11]. CFR was measured in 21 patients at baseline and 1 month after treatment and was found to increase significantly.…”
Section: Dilated Cardiomyopathymentioning
confidence: 98%
“…In particular, Togni et al (20) (21). With the exception of the observation of Gullu (7), where the improvement of CFVR was exclusively due to the decrease of CBF velocities at rest, in the other 4 studies nebivolol increased significantly hyperemic CBF velocities (18)(19)(20)(21). Coronary vasodilation due to either adenosine or dipyridamole is primarily endothelium independent but the increment in CBF may trigger further flow-induced vasodilation, which is endothelium dependent (25,26).…”
Section: Third Generation Beta-blockers (With Vasodilating Action) Anmentioning
confidence: 99%
“…The influence of these two drugs on CFR has been tested in the clinical setting. The improvement of coronary microvascular function obtainable by both carvedilol (14)(15)(16)(17) and nebivolol (7,(18)(19)(20)(21) could be at least one of the substrates underlying the improvement in LV function due to both these drugs. Except for the experience of Koepfli et al (14), where a significant drug-induced increase on PETderived CFR was achieved only pooling 36 patients with coronary artery disease treated by either carvedilol or atenolol (12 week treatment), all the other clinical studies demonstrated a positive effect of carvedilol or nebivolol on CFR (Table 1) (22).…”
Section: Third Generation Beta-blockers (With Vasodilating Action) Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Erdogan et al recently reported that in patients with idiopathic dilated cardiomyopathy one month of oral nebivolol treatment was associated with a significant increase in CFR, as measured by trans-thoracic Doppler echocardiography [6]. Similarly, Galderisi et al have shown that in hypertensive patients free of coronary artery disease, one month of oral nebivolol therapy induces a significant increase in CFR, as assessed by Doppler echocardiography [7].…”
mentioning
confidence: 95%